ANALISIS PERBANDINGAN MAKNA PERIBAHASA MANDARIN INDONESIA YANG MENGANDUNG KATA HEWAN - Subarja, Pandi; Veronica, Tjen; Lusi, Lusi (Universitas Tanjungpura, 2025)
Proverbs have long been used as a means of expressing thoughts and ideas. Animal play an essential role in human life, making them a common elemnt in many proverbs. Both China and Indonesia ar rich in animal species, and this is reflected in their proverbs, which often include animal-related terms. However, due to differences in social, cultural, and traditional aspects, the two nations view animal-related proverbs differently. Thus, this study, titled